2019
DOI: 10.3889/oamjms.2019.177
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Inflammatory Response in Predicting Prostate Cancer: The Diagnostic Value of Neutrophil-To-Lymphocyte Ratio

Abstract: BACKGROUND: Over the past decades, the study of the microenvironment of cancer has supported the hypothesis between inflammation and cancer. Previous studies have demonstrated a promising value of platelet-to-lymphocyte (PLR) and neutrophil-to-lymphocyte ratio (NLR) as a systemic inflammatory response in prostate cancer. AIM: To evaluate their pre-biopsy values of PLR and NLR in predicting prostate cancer. MATERIAL AND METHODS: This is a diagnostic study with retrospective design. We included all b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 14 publications
3
16
0
Order By: Relevance
“…The authors concluded that inflammation had a role in the development of prostate cancer. Kawahara et al, (2015) in a retrospective study reported that the higher the N/L ratio the higher the incidence of prostate cancer as did Adhyatma et al, (2019), while that of Kamali et al, (2018) did not find an association. Our prospective study did not find an associated with clinically significant prostate cancer, and the predictive value was significantly inferior to that of PSA density, free percent PSA and primary CPCs.…”
Section: Discussionmentioning
confidence: 90%
“…The authors concluded that inflammation had a role in the development of prostate cancer. Kawahara et al, (2015) in a retrospective study reported that the higher the N/L ratio the higher the incidence of prostate cancer as did Adhyatma et al, (2019), while that of Kamali et al, (2018) did not find an association. Our prospective study did not find an associated with clinically significant prostate cancer, and the predictive value was significantly inferior to that of PSA density, free percent PSA and primary CPCs.…”
Section: Discussionmentioning
confidence: 90%
“…It is known that the PSA level is not sufficient alone in detecting prostate cancer because it also increases in common diseases such as BPH and prostatitis (11). NLR and PLR, potential markers for determining inflammation, are used for differential diagnosis or prognostic predictors of various diseases such as cancer and inflammatory diseases in many studies (12,13). Leukocytes, mainly lymphocytes, are one of the most significant markers in many cancers, apart from prostate cancer (12,13).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to their use as indicators of systemic inflammatory response in many studies (6,7), it was investigated whether neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) were effective in predicting oncological outcomes in malignancies (8).…”
Section: Introductionmentioning
confidence: 99%
“…Decreased neutrophil count is at risk of poorly differentiated prostate cancer among African Americans [14].A retrospective study by Naito H et al found that PSA and Gleason score had a signi cant association with NLR [15]. ADHYATMA K P et al con rmed NLR has a promising performance in predicting PCa in patients with PSA above 4 ng/dL [16]. However, Kamali K et al found that neutrophil count and neutrophil-to-lymphocyte ratio cannot be predictive factors for positive prostate cancer biopsy [17].…”
Section: Discussionmentioning
confidence: 99%